Sarcomatoid Renal Cell Carcinoma: A Clinical Review - Piotr Remiszewski; Anna Szumera-Ciećkiewicz; Anna M. Czarnecka (Diagnostics, 2026)
This review summarises current evidence on renal cell carcinoma (RCC) with sarcomatoid dedifferentiation (sRCC), with an emphasis on diagnosis, prognostic stratification, and treatment. Sarcomatoid dedifferentiation is characterised by high-grade spindle cell morphology, occurs in 2–26% of all RCC patients, predominantly in the clear cell subtype (~70%), and is WHO/ISUP grade 4 regardless of extent of involvement. Thus, sRCC represents a pathological transformation rather than a distinct entity. Diagnosis requires biopsy or nephrectomy; immunohistochemical (IHC) retention of PAX8, cytokeratins, and vimentin alongside loss of subtype-specific markers distinguishes sRCC from primary renal sarcoma. On CT, sRCC typically presents as a large, heterogeneous mass with extensive necrosis; 18F-FDG PET/CT carries independent prognostic value, though no feature is pathognomonic. Sarcomatoid features are approximately five times more prevalent in patients with metastatic vs. localised disease (~20 vs. ~4%), and their identification should prompt risk stratification. Median overall survival (OS) in metastatic sRCC is 5.9–13.3 months, though recent data suggest improvement with novel therapies. Sarcomatoid dedifferentiation is characterised by enrichment of alterations in TP53, BAP1, CDKN2A/B, and NF2 on a background of founder RCC mutations, generating an immune-inflamed tumour microenvironment with elevated CD8+ T cell infiltration and PD-L1 expression that may underpin the heightened sensitivity of sRCC to immune checkpoint inhibitors (ICI). Surgery remains the cornerstone in localised disease, although recurrence rates approach 80% within two years. Adjuvant pembrolizumab significantly improved disease-free survival in high-risk localised RCC with sarcomatoid features (KEYNOTE-564; NCT03142334). In the metastatic setting, nivolumab plus ipilimumab and pembrolizumab plus axitinib are preferred first-line regimens.